2013
DOI: 10.1517/17425255.2013.759210
|View full text |Cite
|
Sign up to set email alerts
|

Model-based approaches to predict drug–drug interactions associated with hepatic uptake transporters: preclinical, clinical and beyond

Abstract: Static and dynamic models can be convincingly applied to quantitatively predict drug interactions, early in drug discovery, to mitigate clinical risks as well as to avoid unnecessary clinical studies. Compared to basic models, which focus on individual processes, mechanistic models provide the ability to assess DDI potential for compounds with systemic disposition determined by both transporters and metabolic enzymes. However, complexities in the experimental tools and an apparent disconnect in the IVIVE of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 99 publications
0
67
0
Order By: Relevance
“…ATP binding-cassette (ABC) efflux transporters localized on the canalicular membrane of hepatocytes, such as P-glycoprotein (P-gp) (ABCB1), multidrug resistance-associated protein (MRP) 2 (ABCC2), breast cancer resistance protein (BCRP) (ABCG2), and BSEP (ABCB11), are mainly responsible for canalicular secretion (Ishikawa et al, 1995;Muller and Jansen, 1997;Suzuki and Sugiyama, 1999;Chandra and Brouwer, 2004). Based on the analysis of physicochemical property space, ionization state, size, and polarity were noted to be important determinants in the biliary elimination, and these properties are also closely associated with molecular interaction with the hepatic uptake transporters Varma et al, 2012a) The extended clearance equations (Equations 6 and 7) can be applied to get an estimate of the effect of transporter involvement in the hepatic disposition and further to predict the overall hepatic clearance (Liu and Pang, 2005;Barton et al, 2013).…”
Section: Predicting Clearancementioning
confidence: 99%
See 3 more Smart Citations
“…ATP binding-cassette (ABC) efflux transporters localized on the canalicular membrane of hepatocytes, such as P-glycoprotein (P-gp) (ABCB1), multidrug resistance-associated protein (MRP) 2 (ABCC2), breast cancer resistance protein (BCRP) (ABCG2), and BSEP (ABCB11), are mainly responsible for canalicular secretion (Ishikawa et al, 1995;Muller and Jansen, 1997;Suzuki and Sugiyama, 1999;Chandra and Brouwer, 2004). Based on the analysis of physicochemical property space, ionization state, size, and polarity were noted to be important determinants in the biliary elimination, and these properties are also closely associated with molecular interaction with the hepatic uptake transporters Varma et al, 2012a) The extended clearance equations (Equations 6 and 7) can be applied to get an estimate of the effect of transporter involvement in the hepatic disposition and further to predict the overall hepatic clearance (Liu and Pang, 2005;Barton et al, 2013).…”
Section: Predicting Clearancementioning
confidence: 99%
“…6 and 7 using hepatocellularity and liver weight factors (Umehara and Camenisch, 2012;Varma et al, 2013c). Success of mechanistic-based prediction of transportermediated disposition and drug-drug interactions (DDIs) depends upon: 1) the adaptation of experimental tools and study design to obtain in vitro parameters that are relevant in vivo, 2) bridging the functional and protein expression difference between in vitro and in vivo systems, and 3) understanding the uncertainty associated with the parameters obtained from in vitro tools (Barton et al, 2013).…”
Section: Predicting Clearancementioning
confidence: 99%
See 2 more Smart Citations
“…For a long time the study of pharmacokinetics has been largely focused on drug metabolizing enzymes (van Schaik, 2008;Hirota et al, 2013;Samer et al, 2013;Zanger and Schwab, 2013), but increasing evidence has clearly suggested the importance of membrane transporters in pharmacokinetics (Lu et al, 2010;Hua et al, 2012;Barton et al, 2013). For example, disposition of certain cationic drugs may be determined by their uptake via organic cation transporters (OCTs) from circulation to hepatocytes and/or renal tubular cells.…”
Section: Introductionmentioning
confidence: 99%